P‐191L: Late‐News Poster: Solution Processed P‐Channel Oxide Thin Film Transistor Employing Metal Doped Nickel Oxide. Issue 1 (May 2016) - Li, Xiuling; Lin, Tengda; Shin, Jiyeong; Jang, Jin
Abstract : Performance of solution processed p‐channel oxide TFTs are improved by introducing metal‐doping in nickel oxide (NiOx ). On/off current ratio of 5 × 10 4 and field‐effect mobility (µFE ) of ∼0.67 cm 2 /V·s are achieved in the fabricated devices, making it promising for future power efficient oxide circuits and complementary oxide electronics.